MENINGKATKAN KEDISIPLINAN DAN KEMANDIRIAN MELALUI KEGIATAN RUTIN UNTUK KELOMPOK B TK DHARMA WANITA GEGER KECAMATAN KEDUNGADEM KABUPATEN BOJONEGORO - Sriwahyuningsih, Lilik (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to increase independence and discipline Group B1 children at TK Dharma Wanita Geger through routine activities. Activity routinely carried out by practicing habituation, giving motivation, and giving rewards and punishments consistently. This research is a classroom action research conducted collaboratively with classroom teachers conducted in two cycles. Each Cycle consists of planning, action, observation and reflection. Subject in In this study, all children in Group B at TK Dharma Wanita Geger which amounted to 14 children consisting of 10 boys and 4 girls. The object of this research is independence and discipline in students through routine activities. The method of data collection was carried out by observation and documentation. The data analysis technique used is descriptive qualitative and quantitative. The results showed an increase in independence and discipline children from pre-action, Cycle I and Cycle II. The independence of all children before the action is in the moderate criteria, in Cycle I there are 69.23% of children in high criteria, and Cycle II increased to 84.62% of children who achieved very high criteria. While the discipline of children before the action 92.31% of children on moderate criteria, in Cycle I there were 38.46% of children on high criteria, and Cycle II increased to 92.31% of children in very high criteria. With Thus it can be concluded that through routine activities can increase children's independence and discipline